Digital Marketing Communication of Indihome x Telkomsel after Merger - Harliantara; Daniel Susilo (Jurnal Ekonomi dan Bisnis Digital, 2023)
Digital Marketing is always evolving and adapts with people because people themselves are the market. The innovation of this digital marketing is also evolving. Starting from Veronika, we can see Telkomsel x Indihome care about the future. This also counts that modernized content is a good content where we should preserve scientific innovation and content in tech industry and the profit.